Розвиток стратегічних галузей промисловості України в контексті національної економічної безпеки: теоретичні засади - Kozachenko, Ganna V.; Pogorelov, Yuri S. (Institute of Industrial Economics of NAS of Ukraine, 2024)
The article demonstrates the need to identify strategic sectors of industry for the social and economic development of the state, which allows focusing the attention and limited resources of the state on supporting the development of those sectors that ensure national economic security. Within the epistemological contextualism, the concept of "strategic sector" is defined.To classify an industry sector as strategic, proposed criteria are outlined based on objective, sustainable circumstances in the country's economy, and within the context of national economic security. The definition of "national economic security" is provided. The criteria for recognizing the strategic nature of an industrial sector within the context of national economic security are determined by operationalizing constructs derived from the proposed definition of a "strategic industrial sector". Quantitative indicators are proposed to quantitatively describe the degree (intensity) of the criterion for recognizing the strategic nature of an industrial sector within the context of national economic security.The development of the strategic sector of the industry in the context of national economic security is ensured by critical enterprises in the industry. To recognize enterprises in strategic industrial sectors as critical for the industry's development in the context of national economic security, a number of criteria have been proposed. The development of critical enterprises in the industry should be security-oriented in nature.Support and regulation of security-oriented development of enterprises in the strategic industrial complex of Ukraine, which are to include recognized strategically important industries based on proposed criteria for national economic security, should be carried out using a comprehensive mechanism of state regulation of the country's strategic industrial complex. An important element of the comprehensive mechanism of state regulation of the country's strategic industrial complex is the mechanism of state support, which is implemented through various tools distributed among the components of the mechanism.